DEV-11. OUTCOMES OF MALIGNANT BRAIN TUMORS IN YOUNG CHILDREN TREATED WITH CHEMOTHERAPY AND DELAYED RADIOTHERAPY IN A RESOURCE LIMITED SETTING. Issue 2 (22nd June 2018) - KC, Ananda; Sankaran, Hari; Bhat, Vasudev; Shetty, Prakash; Shastry, Jayanth; Sahay, Ayushi; Shridhar, Epari; Mahajan, Abhishek; Prasad, Maya; Vora, Tushar; Pungaonkar, Sona; Moiyadi, Aliasgar; et al.
Abstract: METHODOLOGY: A retrospective analysis of children less than 3 years diagnosed with malignant brain tumors was conducted from January 2011 to December 2016. Children with malignant brain tumors were treated with cyclophosphamide, etoposide and carboplatin (CEJ) upto 36months of age or till disease progression. Low grade gliomas were excluded from the analysis. An intention to treat analysis was performed to determine the outcomes and delay in radiotherapy (RT). RESULTS: ninety four children (median age: 26 months, median follow-up: 18.9 months) were diagnosed with malignant brain tumors of which 59 received the CEJ regimen. Twenty six children (44.0%) underwent a complete resection, 23 (38.9%) partial resection, and 10 (16.9%) debulking/biopsy. Progression free survival (PFS) and overall survival (OS) at 24months was 53.8% (95% CI: 38.6% - 66.9%) and 64.0% (95% CI: 48.7%- 78.8%) respectively.41 children (69.5%) received RT with a median time to delaying RT of 9.3months (inter-quartile range 6.5 -13.4 months). Among 39 cases of medulloblastoma (MB), molecular data was available in 24 (wnt-0, shh-11, group 3 and group4 – 13). The outcomes with shh and non-shh were similar. CONCLUSIONS: Chemotherapy regimens like CEJ are effective in delaying radiotherapy in young children with malignant brain tumors. This approach may be used in resource limited countries to improve the outcomes of young children with malignant brain tumors.